How do you solve #3x^2 – 6x + 3 = 0#?

1 Answer
Aug 2, 2015

Answer:

There is one solution for this expression:
#color(green)(x=1#

Explanation:

#3x^2–6x+3=0#

We can first factorise the above expression and then proceed towards finding the solutions:

Factorising by splitting the middle term

#3x^2–color(green)(6x)+3=0#

#3x^2–color(green)(3x - 3x)+3=0#

#3x(x-1) - 3(x -1)=0#

#(x-1) # is common to both terms.

#color(green)((3x-3) (x-1)# is the factorised form for the expression.

Now we can equate the factors with zero and find the solutions:
#3x-3 = 0 , x=3/3, color(green)(x=1#
#x-1 = 0 , color(green)(x=1#